How to embroider texture and pattern : 20 designs that celebrate pattern, color, and pop-up stitching - Galbraith, Melissa (Landauer Publishing, 2023)
"Channel your love for the outdoors and build your stitching skills by learning how to embroider stunning textures, patterns, colors, and 3D elements in this must-have guide for both beginner to advanced crafters! Featuring 20 step-by-step embroidery projects of beautiful landscapes, desert canyons, unique flora, and more, How to Embroider Texture and Pattern is filled with vibrant embroidery patterns inspired by wanderlust that will challenge and grow your skills as you bring these beautiful outdoor scenes to life. Also included are easy-to-follow tutorials for over 20 need-to-know embroidery stitches, plus guidance for incorporating fabric prints into your projects to enhance the design, textural and 3D embroidery instruction, how to transfer a pattern, and other fundamental techniques. Have fun with color, create rich textures, and feel confident as you stitch your love for nature."--Publisher marketing.